The Analysis of the Influence of Risk Profile, Good Corporate Governance, Earning and Capital (RGEC) towards the Company Value in the Sub-Sector of Foreign Exchange Private National Commercial Bank which is listed on the Indonesia Stock Exchange (IDX) - Evracia Turukay, Maria J.F Esomar, Lilian Loppies (International Journal of Advanced Science and Technology, 2020)
Banking management in the digital age encounters various challenges due to the growing development of the financial and technology industries. Banking management is expected to be able to innovate and maintain the bank’s health. The ability of banking management to maintain the bank’s health will increase the confidence of customers and investors. The bank’s health can be measured using the RGEC method, which assesses aspects of Risk Profile, Good Corporate Governance (GCG), Earning and Capital. This research aims to determine the influence of RGEC towards the company value in foreign exchange national private commercial banks listed on the Indonesia Stock Exchange (BEI) in 2016-2018. In this research, Risk Profile is proxied by NPL, GCG is based on self-assessment, Earning is proxied by ROA and Capital is proxied by CAR. Company value is measured by Price Book Value (PBV). The regression result displays that NPL and GCG have no influence towards company value, while ROA and CAR have an influence towards company value.